Effect of Crosslinking on the Properties of QPVA/PDDA Anion Exchange Membranes for Fuel Cells Application. Issue 4 (27th April 2021) - Samsudin, A. M.; Hacker, V.
Abstract : Anion exchange membranes (AEMs) consisting of quaternary ammonium poly(vinyl alcohol) (QPVA) and poly(diallyldimethylammonium chloride) (PDDA) were prepared by a solution casting method. The influence of the concentration of the chemical crosslinker on the properties and performance of AEMs was investigated. Morphology, chemical structures, thermal and mechanical properties of AEMs were characterized by SEM, FTIR, TGA, and UTM. The performance of AEMs was evaluated by water uptake, swelling degree, ion exchange capacity, and OH − conductivity measurement. The tensile strength, water uptake, and OH − conductivity of AEMs were enhanced with the increase of the crosslinker concentration. By introducing 12.5% glutaraldehyde (GA), the QPVA/PDDA AEMs achieved the highest tensile strength, water uptake, and OH − conductivity of 46.21 MPa, 90.6% and 53.09 ms cm −1 at ambient condition, respectively. The investigations show that crosslinked QPVA/PDDA AEMs are a potential candidate for anion exchange membrane fuel cells.